A Lytic Bacteriophage PS2 with Potential for Controlling Salmonella infections in Chickens and Ducks - Van Quyen, Dong; Lanh, Pham Thi; Oanh, Nguyen Kim; Huong, Pham Vu Thanh (VNU Journal of Science: Natural Sciences and Technology, 2025)
Salmonella is one of the most common and dangerous pathogens, causing significant economic losses to the poultry industry worldwide. It is also a leading cause of foodborne diseases in both humans and animals. To control Salmonella infections, antibiotics are frequently used. In Vietnam, antibiotics are administered not only for disease prevention and treatment but also as growth promoters in livestock. This practice has contributed to the emergence and spread of antibiotic-resistant bacterial strains. Additionally, antibiotic residues in poultry products, such as eggs and meat, pose direct and indirect risks to human. Recently, phage therapy has been explored as a promising alternative to antibiotics for the prevention and treatment of bacterial infections, particularly those caused by antibiotic-resistant strains. In this study, we describe the isolation, selection, and biological characterization of a bacteriophage strain with strong lytic activity against Salmonella enterica subsp. enterica , a causative agent of diarrhea in chickens and ducks in Hai Duong province, Vietnam. The isolated phage strain, PS2, exhibited specific lytic activity against Salmonella and was capable of lysing all 30 tested Salmonella strains. Morphologically, PS2 has Myovirus-like morphology with an icosahedral head of 80.02 ± 3 nm in diameter and a long straight tail of 90.6 ± 8 nm in length. PS2 demonstrated an optimal multiplicity of infection (MOI) of 0.01, a latent phase of approximately 25 minutes, and a burst size of about 225 plaque-forming units (PFU) per cell. Moreover, PS2 maintained stable biological activity across a temperature range of -20 °C to 60 °C and remained stable within a pH range of 5 to 12. Taken together, these results suggest that PS2 is a promising candidate for the development of phage therapy to combat Salmonella infections in poultry in Vietnam.